Nephroprotective Effects of 2nd Type Sodium-Glucose Co-Transporter Inhibitors: A Literature Review - Botir Daminov1, Sherzod Abdullaev2, Rano Igamberdieva3, Olimkhon Sharapov4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: A wide range of oral hypoglycemic drugs with various mechanisms of effect are available forthe treatment of patients with 2nd type diabetes mellitus today. Despite the high effectiveness of these agentsin the normalization of glycemia, they cause different chronic complications in many patients with 2nd typediabetes mellitus. However, during the last years, a range of principal new data has been accumulated onthe pleiotropic effects of the last classes of oral hypoglycemic agents — inhibitors of the 2nd type sodiumglucosecotransporter (SGLT2).Materials and Method: Three electronic databases were checked to find out studies reporting the data onthe mechanisms and clinical significance of the nephroprotective effect of inhibitors of the sodium-glucosecotransporter of 2nd type (glyphlozines) in patients with 2nd type diabetes mellitus. The primary outcomewas to learn the worldwide tendency on this matter and to compare the results of different researchers.Results: We found 25 studies as eligible for our review. The review presents data on the mechanisms andclinical significance of the nephroprotective effect of inhibitors of the sodium-glucose cotransporter of 2ndtype (glyphlozines). The effects associated with the influence of representatives of this pharmacologicalgroup on the glomerular filtration rate, glycemia, diuresis, ketogenesis and other factors are discussed. Theresults of recent experimental and clinical studies aimed at studying certain aspects of the nephroprotectiveeffect of SGLT2 inhibitors in 2nd type diabetes mellitus and other pathological conditions were analyzed.Conclusion. SGLT2 inhibitors associate with a multicomponent nephroprotective effect, which confirmedby the results of both experimental and clinical studies. The nephroprotective potential of SGLT2 inhibitorsis maximally realized in the presence of diabetes and remains not entirely clear in the case of another kidneypathology.